Is it good to be too light? Birth weight thresholds in hospital reimbursement systems - Simon Reif; Sebastian Wichert; Amelie Wuppermann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
Birth weight manipulation is common in DRG systems. Hospitals receive more money for cases with weight below certain thresholds, which could benefit newborns. Also, some reimbursement thresholds overlap with diagnostic thresholds that have been shown to affect medical care. Based on all hospital births in Germany from 2005-2011, we investigate whether this triggers different care. We find that this is not the case, suggesting that financial incentives do not directly impact care for newborns.
Keywords: I110; I180; 330